PENERAPAN MEDIA PEMBELAJARAN INOVATIF TERHADAP PRESTASI BELAJAR PENDIDIKAN AGAMA ISLAM SISWA SEKOLAH MENENGAH PERTAMA UNGGULAN AL FATTAH ANDONG BOYOLALI - Faridatun Niamah; Muhammad Ja'far Nashir (STKIP Pesisir Selatan, 2025)
Islamic Religious Education (IRE) plays a crucial role in shaping students’ moral, spiritual, and intellectual character. However, traditional teaching methods still dominate classroom practice, resulting in low motivation and learning achievement. This study aims to describe the implementation of innovative learning media to improve students’ achievement in Islamic Religious Education for seventh-grade students at SMP Unggulan Al Fattah Andong Boyolali during the 2024–2025 academic year, as well as to identify supporting and inhibiting factors affecting its application. This research employed a qualitative descriptive approach using observation, interviews, and documentation as data collection techniques. Data were analyzed inductively through the stages of data reduction, display, and conclusion drawing following the Miles and Huberman model. The findings reveal that innovative learning media such as Role of Playing, Make A-Match, Examples Non Examples, and Picture on Picture significantly improve students’ motivation, engagement, and academic performance. The main supporting factors include school leadership support, teacher creativity, and a religious learning environment, while the inhibiting factors involve limited digital facilities and variations in student character. The implication of this research indicates that the use of innovative learning media is an effective pedagogical strategy to strengthen character-based Islamic education in the digital era.